Estimating the pre- and post-diagnosis costs of tuberculosis for adults in Pakistan: household economic impact and costs mitigating strategies - Shama Razzaq; Aysha Zahidie; Zafar Fatmi (Global Health Research and Policy, 2022)
Abstract Background Despite free tuberculosis (TB) care in Pakistan, patients still have to bear high costs, which push them into poverty. This study estimated the pre- and post-diagnosis costs households bear for TB care, and investigated coping mechanisms among adults ≥ 18 years in Karachi, Pakistan. Methods We conducted a cross-sectional study comprising of 516 TB patients identified with completion of at least one month intensive treatment from four public sector health facilities from two institutes in Karachi, Pakistan. A standardized questionnaire to estimate patient's costs was administered. The study outcomes were direct medical and non-medical costs, and indirect costs. The costs were estimated during pre-diagnostic and post-diagnostic phase which includes diagnostic, treatment, and hospitalization phases. A descriptive analysis including mean and standard deviation (± SD), median and interquartile range (IQR), and frequencies and proportions (%) was employed. Results Out of 516 TB patients, 52.1% were female with a mean age of 32.4 (± 13.7) years. The median costs per patient during the pre-diagnostic, diagnostic, treatment and hospitalization periods were estimated at USD63.8/ PKR7,377, USD24/ PKR2,755, USD10.5/ PKR1,217, and USD349.0/ PKR40,300, respectively. The total household median cost was estimated at USD129.2/ PKR14,919 per patient. The median indirect cost was estimated at USD52.0/ PKR5,950 per patient. Of total, 54.1% of patients preferred and consulted private providers in the first place at the onset of symptoms, while, 36% attended public healthcare services, 5% and 4.1% went to dispensary and pharmacy, respectively, as a first point of care. Conclusions TB patients bear substantial out-of-pocket costs before they are enrolled in publically funded TB programs. There should be provision of transport and food vouchers, also health insurance for in-patient treatment. This advocates a critical investigation into an existing financial support network for TB patients in Pakistan towards reducing the burden.